PENGARUH DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASIONAL DI SMP NEGERI SE KECAMATAN PATI KABUPATEN PATI - Peni Widi Astuti, 12.5202.0124 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimed to examine the effect of labor discipline and competence of the teachers performance in the organizational commitment mediated SMP at Pati District. Selection of respondents who performed with proportionale stratified random sampling of 179 people.Data were collected using a questionnaire, after which the data were processed using SPSS 19th disipin results showed a positive and significant effect on organizational commitment, competence and a significant positive effect on organizational commitment, discipline and no significant positive effect on teacher performance, competencies influence positively and significant impact on teacher performance, organizational commitment and no significant positive effect on teacher performance. Keywords: Discipline, Competence, Organizational Commitment, Performance